Availability of integrated family planning services in HIV care and support sites in sub-Saharan Africa: A secondary analysis of national health facility surveys - Laar, A.; Kanyangarara, M.; Sakyi, K. (Reproductive Health, 2019)
Background: Integrating family planning (FP) with HIV care and treatment programs is a strategy to expand FP service delivery and prevent unintended pregnancies among women living with HIV. However, little is known about the extent to which FP services are available in health facilities providing HIV services across sub-Saharan Africa. In this study, we assessed the availability of integrated FP services and the associated factors in HIV care and support sites across sub-Saharan Africa. Methods: We conducted a secondary analysis of nationally representative facility-level data from Service Availability and Readiness Assessments (SARA) and Service Provision Assessments (SPA) conducted in 10 sub-Saharan African countries between 2012 and 2015. We used six indicators that reflect the structure and process of care essential for FP service delivery in HIV care and support facilities to define the outcome of interest - onsite availability of integrated FP services. Multivariate logistic regression was used to explore facility-level characteristics associated with the outcome. Results: Among the 3161 health facilities offering HIV care and support services, most reported also offering FP services at the same location. The availability of three FP methods was higher than the availability of FP guidelines and trained staff. Onsite availability of integrated FP services ranged from 10 to 61%. Results of multivariate logistic regression indicated that the odds of having onsite integrated FP services available was higher in HIV care and support sites that were operated by the government, classified as a tertiary level care facility, and provided services for PMTCT, antenatal care and basic surgery. Conclusions: Our findings indicate critical shortcomings in the preparedness of HIV care and support sites to deliver onsite integrated FP services. Renewed efforts are needed to address these supply-side barriers and ensure that integrated FP and HIV services meet the unique needs of HIV clients.
\Research Article
Keywords: HIV; Family planning; Sub-Saharan Africa; Health facility surveys